AN INTERACTION MODEL BETWEEN ENVIRONMENTAL FACTORS AND BLACK RICE GROWTH IN IRRIGATED ORGANIC PADDY FIELD - Budiman Budiman; Endang Arisoesilaningsih (AGRIVITA, Journal of Agricultural Science, 2015)
Black rice production in organic farming system does not meet the demand of local customers because of its low productivity. This research aimed to set an interaction model using multivariate analysis via smartPLS to identify environmental factors which simultaneously affects the growth of black rice. The growth of black rice in two irrigated organic paddy field in Malang, Indonesia was observed during planting period from November 2011 to March 2012. In each rice field, the growth was periodically recorded during planting periods: 19-29 days after planting (dap), 41-45 dap, 62-66 dap, 77-81 dap, 90-94 dap and 104-106 dap. Environmental factors such as water quantities, soil conditions, weed communities and cultivation system around the black rice population were also measured. Black rice growth was influenced simultaneously by water quantities, soil, weed communities and cultivating systems with predictive-relevance value reaching 92.83%. Based on the model, water quantities in paddy field is a key factor which directly and indirectly determined the growth and productivity of black rice.